Evaluation of the novel USPIO GEH121333 for MR imaging of cancer immune responses. (13th March 2013) - Shi, Qiaoyun; Pisani, Laura J.; Lee, Yauk K.; Messing, Solomon; Ansari, Celina; Bhaumik, Srabani; Lowery, Lisa; Lee, Brian D.; Meyer, Dan E.; Daldrup‐Link, Heike E.
Abstract : Tumor‐associated macrophages (TAM) maintain a chronic inflammation in cancers, which is associated with tumor aggressiveness and poor prognosis. The purpose of this study was to: (1) evaluate the pharmacokinetics and tolerability of the novel ultrasmall superparamagnetic iron oxide nanoparticle (USPIO) compound GEH121333; (2) assess whether GEH121333 can serve as a MR imaging biomarker for TAM; and (3) compare tumor MR enhancement profiles between GEH121333 and ferumoxytol. Blood half‐lives of GEH121333 and ferumoxytol were measured by relaxometry ( n =  4 each). Tolerance was assessed in healthy rats injected with high dose GEH121333, vehicle or saline ( n =  4 each). Animals were monitored for 7 days regarding body weight, complete blood counts and serum chemistry, followed by histological evaluation of visceral organs. MR imaging was performed on mice harboring MMTV‐PyMT‐derived breast adenocarcinomas using a 7 T scanner before and up to 72 h post‐injection (p.i.) of GEH121333 ( n =  10) or ferumoxytol ( n =  9). Tumor R 1, R 2 * relaxation rates were compared between different experimental groups and time points, using a linear mixed effects model with a random effect for each animal. MR data were correlated with histopathology. GEH121333 showed a longer circulation half‐life than ferumoxytol. Intravenous GEH121333 did not produce significant adverse effects in rats. All tumors demonstrated significant enhancement on T 1, T 2 and T 2 *‐weighted images at 1, 24, 48 and 72 h p.i. GEH121333 generated stronger tumor T 2 * enhancement than ferumoxytol. Histological analysis verified intracellular compartmentalization of GEH121333 by TAM at 24, 48 and 72 h p.i. MR imaging with GEH121333 nanoparticles represents a novel biomarker for TAM assessment. This new USPIO MR contrast agent provides a longer blood half‐life and better TAM enhancement compared with the iron supplement ferumoxytol. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Summary of key findings : GEH121333 could be used as an imaging biomarker for TAM. This novel, dedicated MR contrast agent showed an excellent safety profile in rodents and better signal enhancement compared with the iron supplement ferumoxytol.